A Y-chromosome portrait of the population of Jerba (Tunisia) to elucidate its complex demographic history - Franz Manni; Pascal Leonardi; Étienne Patin; Alain Berrebi; Houssein Khodjet el Khil; Karl Skorecki; Dror Rosengarten; Hassan Rouba; Evelyne Heyer; Marc Fellous (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The Island of Jerba has a long demographic history that is related to its central position in the Mediterranean Sea. The island was in contact with different civilizations and its population is heterogeneous (Arabs, Berbers, black Africans and Jews).We sampled 127 males (Jewish sample N = 32; Berber sample N = 46; Arab sample N = 47) in order to identify the Y-chromosome variability of the population according to 10 Unique Event Polymorphisms (UEPs): SRY-2627; SRY-10831a; SRY-4064; 92R7; Tat; YAP; M2; LLY22g; M9; 12f2q. We also sampled the Black group living in Jerba but typing ambiguities forced us to exclude it from further analyses.The results suggest a very low degree of genetic differentiation between Jerban Arabs and Berbers, who can be considered genetically, as belonging to the same group. In contrast, pairwise FST measures show that the genetic distances between the Jewish sample and the other ethnic groups are the highest in the island. This datum implies a low level of gene flow between the different communities that reside in Jerba, with the exception of Arabs and Berbers. Since geographic isolation plays no role, the different allelic profiles of the three ethnic groups are related to their different geographic origins, which are likely to have been maintained by the cultural differences existing between Arabs, Berbers and Jews.By comparing the observed haplogroup profiles with 19 reference populations located around the Mediterranean basin, we confirm a North African origin for the Berber and Arab sample and a Middle Eastern ancestral population for Jerban Jews.